Impeded Opportunities: The Content and Consequences of Structures Constraining Supervisors' Communication With Older Workers. (August 2019) - Kroon, Anne C.
Supervisors are confronted with the challenge to support the employability of rapidly aging teams. Drawing on structuration theory, two studies construct and test a conceptual model of how structures (rules and resources) constraining supervisors' communication with older workers impede older workers' job performance and access to promotion. A set of constraining structures was qualitatively identified through in-depth interviews and subsequently quantified in a survey. The results reveal a set of constraining structures that obstruct supervisors' conversations with older workers and consequently hinder employability outcomes. If older workers are to take advantage of national and organizational policies and resources aimed at improving their employability, these constraining structures should be targeted.